Serum Malondialdehyde, Gamma Glutamyl Transferase and Prostate Specific Antigen as Markers of Cancer of the Prostate - OPARINDE, Dolapo Pius; ATIBA, Adeniran Samuel; ADEGUN, Patrick Temi; ‘Niran-Atiba, Temitope Adeola (The International Journal of Biotechnology, 2013)
OBJECTIVE: Prostate specific antigen (PSA) has been found not to be specific for the screening of cancer of the prostate (CaP). We determined serum levels of prostate specific antigen, malondialdehyde (MDA) and gamma glutamyl transferase in patients with newly diagnosed CaP and benign prostatic hyperplasia (BPH) DESIGN: A cross sectional study SETTING: It was carried out in the urology clinic of Ladoke Akintola University of Technology Teaching Hospital, Osogbo, Nigeria SUBJECTS: A total of 67, 50 and 70 men for patients with BPH, CaP and healthy age matched control respectively were recruited. RESULTS: Serum MDA(µmol/l) was observed to be significantly higher in CaP(2.05±0.64) than in BPH (1.68±0.41); p<0.05. There were also a significant higher value of serum MDA in CaP(p<0.01) and BPH(p<0.05) when compared with control (0.06±0.09). Significant higher serum levels of PSA (ng/ml) was observed in patients with CaP (70.25±50.40) than patients with BPH (22.77±10.17); p<0.01. Serum PSA(ng/ml) also was found to be significantlly higher in CaP(p<0.01) as well as BPH (p<0.01) when compared with control (0.76±0.54). There was a significant positive correlation between serum MDA and PSA in patients with CaP(r=0.701;p<0.05) and BPH (r=0.651;p<0.05). There were no significant differences in serum GGT among the study groups CONCLUSSION: Serum level of malonaldehyde may be used as a marker in screening for prostate cancer as a compliment to PSA. Gamma glutamyl transferase may have no place in prostatic cancer detection.